KARAKTERISTIK MUTU KECAP KEPALA UDANG DENGAN VARIASI VOLUME EKSTRAK NANAS DAN WAKTU INKUBASI - Lina Widawati; Ki Ageng Sanjaya (University of Prof. Dr. Hazairin, SH, 2019)
Shrimp head has a high protein content (25-40%,) so that Shrimp head can be processed into fish sauce. The purpose of this study was tocharacterize the quality of shrimp head sauce through proteins, viscicity, and organoleptics analysis.The results showed that shrimp head sauce protein all treatment have meet quality standards,that is above 2,5%. The highest shrimp head sauce protein content is on the treatment of 15% pineapple extract volume variation and incubation time for 24 hour, which is equal to 5,893%. From the results of the study, it can be seen that the highest viscosity value is the treatment of 15% pineapple extract volume with a 24-hour incubation time of 33,260 cP. From the results of the study, it can be seen that the highest viscosity value is the treatment of 15% pineapple extract volume with a 24-hour incubation time of 33,260 cP. The highest organoleptic results for the color, taste, and thickness of shrimp head soy sauce were 15% pineapple extract volume treatment and 24 hour incubation time with color values ??4.6 (very like), taste value 4.05 (likes) and thickness 4, 65 (really like).